2012
DOI: 10.1364/ao.51.003787
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of imaging Fabry–Perot interferometers for measuring upper-atmospheric temperatures and winds

Abstract: We apply an onion-peeling inversion to simulated imaging Fabry-Perot interferometer (FPI) observations for retrieving altitude profiles of neutral temperatures and winds in the thermosphere in order to investigate the effects of realistic gradients in thermospheric parameters on the retrieved parameters. A forward model is developed that simulates the interference spectrum observed by an FPI using the redline (630.0 nm) and greenline (557.7 nm) emissions simulated based on climatological models. This forward m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently, our research group reported the Pd-catalyzed decarboxylation acylation of Nacetyl-1,2,3,4-tetrahydroquinolines. 12 In addition, the visiblelight-induced catalytic system has served as an increasingly significant role in the design and development of a variety of radical reactions under observably mild reaction conditions. 13 From the above, the combination of transition-metal catalysis mode with visible-light-induced catalytic system was tried in this work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, our research group reported the Pd-catalyzed decarboxylation acylation of Nacetyl-1,2,3,4-tetrahydroquinolines. 12 In addition, the visiblelight-induced catalytic system has served as an increasingly significant role in the design and development of a variety of radical reactions under observably mild reaction conditions. 13 From the above, the combination of transition-metal catalysis mode with visible-light-induced catalytic system was tried in this work.…”
Section: ■ Introductionmentioning
confidence: 99%